PERAN HUBUNGAN MASYARAKAT PEMERINTAH KOTA SALATIGA DALAM MEMFASILITASI TERLAKSANANYA UU NO.14 TAHUN 2008 TENTANG KETERBUKAAN INFORMASI PUBLIK - Sariayu, Viona Alamanda; Sandang, Yesaya; Mayopu, Richard G. (Universitas Kristen Satya Wacana, 2018)
Communication is a process of transmitting messages from sources to recipients through various channels. While the purpose of human communication is to share experience and knowledge, delivered in the language of signals, words, writing, movement, and broadcasting. The results of the process are created a theory named diffusion of information, also stands for innovation diffusion theory. for some institution, the task is the duty of a Public Relations. In performing its job, as of 2010 the Public Relations motion was increasingly 'supervised' by the constitutional Law No.14 of 2008, as well as Public Relations of Salatiga Local Government. This research was conducted in Public Relations of Salatiga Local Government for two months of observation and interviewing using a qualitative approach especially grounded theory research. Data triangulation was conducted at the Department of Transportation, Communication, Culture, and Tourism (Dishubkombudpar) in Salatiga and interviews with two of the four Chairmen of the Forum of Public Communication Institutions (FLKM) in Salatiga. In addition, the implementation of Law on the Openness of Public Information in Salatiga is not reserve in accordance with the Mayor's Decree No. 950/434/2012 and information management guidelines and documentation for officials at the State Public Agency Central and Regional Level (Issued by the Ministry of Communication and Information Indonesia).